Self-healing strategy for distribution networks with AC flexible interconnection devices - Ni, Xiaojun; Lu, Yi; Ding, Chao; Shang, Yufei; Wang, Zihan (Frontiers in Energy Research, 2025)
The closing-loop and splitting-loop operations of sectionalizing switches and tie switches serve as crucial means for self-healing in distribution network feeder areas. However, the inrush currents generated during closing-loop operations impact the secure and stable operation of distribution networks. To address these challenges, this paper analyzes the effects of steady-state circulating currents and closing-loop inrush currents caused by tie-switch operations on loop-closing branches. Leveraging the dynamic compensation characteristics of AC flexible interconnection devices (FIDs), we elucidate the working principles of FID-based distribution network self-healing and propose an inrush-current-free closing-loop method utilizing FIDs. For distribution networks incorporating wind and solar resources, constraints characterizing line power flow, nodal voltage, branch capacity, and network topology are established, forming a multi-objective optimization model for self-healing that considers renewable energy accommodation capacity. Finally, case studies demonstrate the effectiveness of the proposed self-healing scheme in enhancing renewable energy accommodation capabilities.